2007
DOI: 10.2514/1.27499
|View full text |Cite
|
Sign up to set email alerts
|

Active Control of a Mach 0.9 Jet for Noise Mitigation Using Plasma Actuators

Abstract: Localized arc filament plasma actuators were used to control an axisymmetric Mach 0.9 jet with a Reynolds number based on the nozzle exit diameter of 7:6 10 5. Eight actuators, distributed azimuthally inside the nozzle, near the nozzle exit, were used to excite various instabilities and azimuthal modes of the jet over a large Strouhal number range (St DF of 0.1 to 5.0). Time-resolved pressure measurements were used to investigate the development of actuation perturbations in the jet, particle image velocimetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
103
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(113 citation statements)
references
References 59 publications
9
103
1
Order By: Relevance
“…The need for such a physical understanding is motivated by ongoing efforts from the beginning of civil air traffic with jet engines to suppress jet noise from engine exhausts leading to larger bypass ratios of the jet engine, geometrical modifications of the nozzle trailing edge and active control devices like plasma actuators, microjets, fluidic chevrons and for acoustic forcing (see e.g. reviews in Tam 1998;Samimy et al 2007;Jordan & Gervais 2008;Laurendeau et al 2008). Yet an intuitive understanding of the noiseproducing structures is still in its infancy after more than five decades of jet noise research (see e.g.…”
Section: Downloadedmentioning
confidence: 99%
“…The need for such a physical understanding is motivated by ongoing efforts from the beginning of civil air traffic with jet engines to suppress jet noise from engine exhausts leading to larger bypass ratios of the jet engine, geometrical modifications of the nozzle trailing edge and active control devices like plasma actuators, microjets, fluidic chevrons and for acoustic forcing (see e.g. reviews in Tam 1998;Samimy et al 2007;Jordan & Gervais 2008;Laurendeau et al 2008). Yet an intuitive understanding of the noiseproducing structures is still in its infancy after more than five decades of jet noise research (see e.g.…”
Section: Downloadedmentioning
confidence: 99%
“…Originally these actuators were developed to control high-speed, high-Reynolds number jets for mixing enhancement and noise mitigation. [19][20][21] LAFPAs assert their control in the jet by using natural instabilities in the flow to amplify the generated perturbations. This report details the investigation of the LAFPA's control authority in a SWBLI.…”
Section: Current Active Control Researchmentioning
confidence: 99%
“…Samimy (Samimy et al, 2007a) for instance experimentally observed similar spectral peaks using localized arc filament plasma actuators. Broadband noise modification with the two different forcing frequencies Fig.…”
Section: Pulsed Microjetsmentioning
confidence: 71%
“…The two forcing frequencies f F = 3 kHz and 9 kHz are considered for the simulations. They are chosen following the experimental results of Samimy (Samimy et al, 2007a) using localized arc filament plasma actuators and who observed a broadband noise increase for the low frequency excitation and a reduction for the high one.…”
Section: Simulated Configurations and Numerical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation